Peningkatkan Hasil Belajar PKn Siswa SD Menggunakan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) - Kurniasih, Try Indiastuti; Elvadola, Connyta (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
This study aims to improve the learning outcomes of elementary school students by using the Student Team Achievement Division (STAD) cooperative learning model in Citizenship Education subjects with Pancasila class VI material at SD Negeri Sukamenanti Bandar Lampung. This type of research is Classroom Action Research that uses qualitative data, and the reference used as a guide for this research is the Kemmis and MC model of classroom action research. Taggart which includes planning, action, implementation of action and observation, and reflection. The results of research conducted in class VI SD Negeri 2 Sukamenanti Bandar Lampung. With the research subject of 20 students and homeroom teachers, it can be said that it is going well. By applying the cooperative learning model type Student Team Achievement Division (STAD) can improve student learning outcomes, it is evidenced by the increase in student learning outcomes that occurred in the first cycle on average (70%) and became (95%) in the second cycle. By applying the cooperative learning model of the Student Team Achievement Division (STAD) type according to the stages, it can have a major influence on student learning outcomes.